Defect engineering-mediated Co9S8 with unexpected catalytic selectivity for heterogeneous Fenton-like reaction: Unveiling the generation route of 1O2 in VS active site - Zhimo Fang; Juanjuan Qi; Wenxing Chen; Lin Zhang; Jianhui Wang; Caili Tian; Qin Dai; Liu, Wen; Lidong Wang (Applied Catalysis B: Environmental, 2023)
Singlet oxygen (1O2) plays a crucial role in Fenton-like reactions due to its high efficiency and selectivity in removing trace organic pollutants from complex water matrices. Defect engineering, which allows the efficient exposure of active sites and optimization of electronic structures, has rapidly emerged as a fundamental strategy for enhancing 1O2 yield. Herein, we introduce tunable sulfur vacancy (VS) density into Co9S8 catalysts for peroxymonosulfate (PMS) activation. The modulation of the octahedral Co (CoS6) and tetrahedral Co (CoS4) electronic structures by VS triggers the unexpected selective generation of 1O2. The VS/PMS system exhibits excellent resistance to interference and highly selective degradation of electron-donating organic pollutants. Experimental and theoretical calculations revealed a new evolutionary route for 1O2 involving two phases (Phase I: HSO5− → *O, Phase II: *O + HSO5− →*OO → 1O2). This study provides a molecular-level understanding of VS-mediated catalytic selectivity for high-efficient decontamination applications.
Keywords: Electronic structure; Generation mechanism; Singlet oxygen; Sulfur vacancy; Theoretical calculation